Modeling and integration of a heat storage tank in a compressed air electricity storage process. (October 2015) - Kéré, A.; Goetz, V.; Py, X.; Olives, R.; Sadiki, N.
Highlights: Large-scale heat storage tank behavior is explored with a two dimensional model. Thermal storage tank efficiencies are estimated thanks to dimensionless numbers. Abacuses of the tank efficiency are provided. The link between tank efficiency and A-CAES global efficiency is generated. Abstract: In an adiabatic compressed air energy storage process (A-CAES), heat storage tank operation is a key factor that determines the overall energy performance of the process. To highlight energy issues linked to a correct tank design in the specific case of an A-CAES system, a two-dimensional thermal numerical model was developed. Thermal efficiencies of the tank are presented with abacus defined from the four dimensionless numbers defining the thermal behavior of the reservoir. Cycling effects are explored with a realistic case study corresponding to an A-CAES system design to deliver an electrical power of 250 MWel for 4 h, the daily peak demand. Extended beyond the thermal reservoir, A-CAES thermodynamic analysis combined with the dynamic simulation makes it possible to generate a direct quantitative link between reservoir sizing and A-CAES global efficiency.